UNTIL IT IS NO LONGER THERE - Przybylski, Ryszard (Porównania, 2015)
Deletion has become part and parcel of the modern arts. A case in point is erasing Robert Rauschenberg’s drawing by Willem de Kooning. Erasing did not merely boil down to an act of destruction but became a symbol of openness to the new. Taking such a perspective towards the avant-garde experience of art, it can be assumed that Kazimierz Malewicz had a similar goal with the black square with the white background. This is also an example of the deletion of a traditional understanding of art in order to prepare for a new expe-rience of art. These experiences undermine the signficance of visibility itself and lead straight to an openness towards tactility.